RELIGIOUS THOUGHT IN CENTRAL ASIA: IT NEEDS A MAJOR OVERHAUL - KHAKIM, Abdullo (CENTRAL ASIA AND THE CAUCASUS, 2005)
Islam, one of the most stable aspects of Central Asia today, has a considerable influence on the local historical and sociopolitical processes and their trends. Its potential and stability are rooted in the unique combination of historical and political circumstances that add legitimacy to Islam and ensure its future. Islam as an important strategic factor cannot be excluded from the region’s social and political life: all the Central Asian countries are doing their best to make it more constructive and to use its huge physical and moral potential to build democratic nation-states. Today, Islam in Central Asia is very conservative and steeped in tradition; while still an important factor in the present sociopolitical context, it is experiencing a crisis created by the gap between the type and level of religious awareness and the realities of developed contemporary society. Being weak intellectually and lacking structure, Islam is unable to play the constructive and creative function inherent in it. This explains why in Central Asia its role is not always positive; more often than not this negatively affects the sociopolitical processes there. The pernicious results are clearly demonstrated by two very important aspects. First, while the level of religious awareness in a society that is behind the times remains low, religion, with its untapped potential, is degenerating from a consolidating factor into a factor of instability and radicalism. Second, Islam has still not become a driving force of nation-state formation. This deprives the process of Islam’s omnipotent physical and moral potential and could also deprive future political regimes of legitimacy. It stands to reason that against the background of the permanently active Islamic factor the present crisis in religious thinking will most likely lead to negative moral, cultural, social, and political phenomena, including religious radicalism and extremism with political overtones. Religious awareness and religious thought should be raised to a level where religion will not only stop feeding conflicts (a role which does not belong to it), but also play a constructive role in creation and consolidation. This adds urgency to the problem of reforming religious thinking and of modernizing the Islamic factor as a precaution against radicalization of religion and a guarantee of its sustainable development. To achieve that we need a set of programs related to the following issues: (1) improved mechanisms for regulating relations between the state and religion, as well as the legal basis of Islam’s social functioning. (2) structural and meaningful changes in the sphere of religious education. (3) modernization of religious enlightenment. (4) improvement of the imperfect Muslim clergy institution, etc.